2007
DOI: 10.1089/ars.2007.9.143
|View full text |Cite
|
Sign up to set email alerts
|

Higher Leukocyte 8-Oxo-7,8-Dihydro-2'-Deoxyguanosine and Lower Plasma Ascorbate in Aging Humans?

Abstract: Is oxidative damage of DNA responsible for physiological changes associated with aging? The authors note a positive correlation between the age of human subjects with the level of 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) in leukocyte DNA. The levels of urinary 8-oxo-7,8-dihydroguanine and 8-oxodG followed the same pattern of correlation. Age-dependent decline in the concentration of plasma vitamin C was also evident. These interesting observations in humans point towards the need to scrutinize in detail t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 36 publications
0
61
0
2
Order By: Relevance
“…Urine samples were frozen at −85°C and stored for no more than 1 month. The precise description of the method that was used for quantitative assessment was given previously (10). The levels of creatinine has been determined colorimetrically by the Jaffe reaction.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Urine samples were frozen at −85°C and stored for no more than 1 month. The precise description of the method that was used for quantitative assessment was given previously (10). The levels of creatinine has been determined colorimetrically by the Jaffe reaction.…”
Section: )mentioning
confidence: 99%
“…The blood with cells was carefully applied on top of Histopaque 1119 solution (Sigma), and leukocytes were isolated by centrifugation according to the procedure described by the manufacturer. Quantification of 8-oxodG in DNA isolates was described previously (10). Since it was recently shown that the extent of artifactual formation of 8-oxodGua is inversely dependent on the amount of extracted DNA, we used only those samples for which the quantity of DNA extracted was in the range 100 to 300 μg.…”
Section: )mentioning
confidence: 99%
“…5 Determination of 8-oxodG by the mean of HPLC/EC technique was described previously. 5,6 Urine analysis Urine sample preparation, HPLC purification and GC/MS analysis were conducted as described earlier. 5 …”
Section: Dna Isolation and 8-oxodg Determination In Dna Isolatesmentioning
confidence: 99%
“…5,6 Urine analysis Urine sample preparation, HPLC purification and GC/MS analysis were conducted as described earlier. 5 …”
Section: Dna Isolation and 8-oxodg Determination In Dna Isolatesmentioning
confidence: 99%
“…The concentrations of 8-hydroxy-2'-deoxyguanosine (8-OHdG) in the liver were measured by the modified Foksiński method [22] using high--performance liquid chromatography -ultraviolet and electrochemical detectors (HPLC/UV/ECD). DNA hydrolysates were analyzed by isocratic elution chromatography using 25 mM sodium acetate, 12.5 mM citrate (pH 5.0)-methanol (88:12, v/v).…”
Section: Liver Tissue Sampling and Testingmentioning
confidence: 99%